THE RELATIONSHIP BETWEEN LEARNING MOTIVATION AND LEARNING ENVIRONMENT AT HOME ON MATHEMATICS LEARNING OUTCOMES IN STUDENTS CLASS VIII IN SMP MUHAMMADIYAH 1 DEPOK SLEMAN - Yeni Widdihastuti; Uus Kusdinar (Universitas Ahmad Dahlan, 2017)
Student learning outcomes are determined by many factors. Motivation to learn and the learning environment at home are some of the factors that relate to student learning outcomes. This research aims to know about is there any positive correlation and significance or not between motivation to learn and learning environment at home on mathematics learning outcomes in students class VIII of SMP Muhammadiyah 1 Depok Sleman in even semester in the academic year of 2016/2017. The population in this research was the students of VIII grade in SMP Muhammadiyah 1 Depok Sleman in the academic year of 2016/2017, consisted of class VIIIA, VIIIB, VIIIC, VIIID totaling 149 students. Samples were taken from VIIIC as the research sample class and with the purposive sampling technique. The writer uses a questionnaire method to collect the data of motivation to learn and the learning environment at home and test method the resulting learning of math. The research instrument: validity test and reliability test. Test requirement analysis includes a test of normality, test of linearity, and the test of independence. The writer uses product-moment correlation analysis and multiple linear regression analysis to analyze the data. The results showed that there was a positive and significant relationship between motivation to learn and learning environment at home outcomes in students class VIII in even Semester of SMP Muhammadiyah 1 Depok Sleman in the academic year of 2016/2017. It is showed by Fcount Ftable is 5,126 > 3,276 with R = 0,481 and R2 = 0,232 with with SR dan SR , SE = , SE .